2016
DOI: 10.1186/s12970-016-0133-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of powdered Montmorency tart cherry supplementation on acute endurance exercise performance in aerobically trained individuals

Abstract: BackgroundThe purpose of this study was to determine whether short-term supplementation of a powdered tart cherry supplement prior to and following stressful endurance exercise would affect markers of muscle damage, inflammation, oxidative stress, and/or muscle soreness.Methods27 endurance-trained runners or triathlete (21.8 ± 3.9 years, 15.0 ± 6.0 % body fat, 67.4 ± 11.8 kg) men (n = 18) and women (n = 9) were matched based on average reported race pace, age, body mass, and fat free mass. Subjects were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 47 publications
7
84
0
3
Order By: Relevance
“…Of the 2 studies investigating the influence of MC supplementation on exercise performance to date, 1 reported improved performance in males completing a half-marathon (21.1 km) run, as evidenced by a faster overall race pace compared to the PLA group. 19 However, as previously mentioned, there were some limitations to the study design, and therefore, these results should be interpreted with a degree of caution. While Levers et al 19 designed an experiment to assess the influence of ingesting 480 mg of powdered tart cherries for 10 days, including supplementation on race day up to 48 hour post-run, we investigated the effects of a single dose (60 mL) of MC concentrate on exercise performance using a crossover study design.…”
Section: Influence Of MC Supplementation On Performancementioning
confidence: 84%
See 2 more Smart Citations
“…Of the 2 studies investigating the influence of MC supplementation on exercise performance to date, 1 reported improved performance in males completing a half-marathon (21.1 km) run, as evidenced by a faster overall race pace compared to the PLA group. 19 However, as previously mentioned, there were some limitations to the study design, and therefore, these results should be interpreted with a degree of caution. While Levers et al 19 designed an experiment to assess the influence of ingesting 480 mg of powdered tart cherries for 10 days, including supplementation on race day up to 48 hour post-run, we investigated the effects of a single dose (60 mL) of MC concentrate on exercise performance using a crossover study design.…”
Section: Influence Of MC Supplementation On Performancementioning
confidence: 84%
“…However, as previously mentioned, there were some limitations to the study design, and therefore, these results should be interpreted with a degree of caution. While Levers et al designed an experiment to assess the influence of ingesting 480 mg of powdered tart cherries for 10 days, including supplementation on race day up to 48 hour post‐run, we investigated the effects of a single dose (60 mL) of MC concentrate on exercise performance using a crossover study design. Despite the differences in dosing strategies, both studies reported improvements in performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire developed in our lab and reported in numerous previously published papers [23, 4649] was used to assess side effects in this study. Participants completed the survey every week throughout the study to determine how well participants tolerated supplementation; how well participants followed the supplementation protocol; and, if participants experienced any symptoms during the supplementation period.…”
Section: Methodsmentioning
confidence: 99%
“…Tart cherry has been shown to reduce markers of inflammation [134], decrease perceptions of soreness [129], and improve redox balance [134] compared with placebo after exercise. Pomegranate juice has been shown to reduce muscle soreness and weakness in elbow flexors following an eccentric elbow flexion protocol [132].…”
Section: Micronutrientsmentioning
confidence: 99%